2021
DOI: 10.1126/scitranslmed.abd1525
|View full text |Cite
|
Sign up to set email alerts
|

Development and deployment of COVID-19 vaccines for those most vulnerable

Abstract: Development of safe and effective COVID-19 vaccines is a global priority and the best hope for ending the COVID-19 pandemic. Remarkably, in less than 1 year, vaccines have been developed and shown to be efficacious and are already being deployed worldwide. Yet, many challenges remain. Immune senescence and comorbidities in aging populations and immune dysregulation in populations living in low-resource settings may impede vaccine effectiveness. Distribution of vaccines among these populations where vaccine acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 130 publications
(98 reference statements)
0
63
0
2
Order By: Relevance
“…The COVID-19 pandemic has revealed massive inequities in health care and in vaccine access that must be confronted to ensure health for all ( Fontanet et al., 2021 ; Koff et al., 2021 ; Subbarao, 2020a ; Wouters et al., 2021 ), but these topics are beyond the scope of this review. At the request of the World Health Assembly, the WHO appointed an Independent Panel for Pandemic Preparedness and Response.…”
Section: The Path(s) Forwardmentioning
confidence: 99%
“…The COVID-19 pandemic has revealed massive inequities in health care and in vaccine access that must be confronted to ensure health for all ( Fontanet et al., 2021 ; Koff et al., 2021 ; Subbarao, 2020a ; Wouters et al., 2021 ), but these topics are beyond the scope of this review. At the request of the World Health Assembly, the WHO appointed an Independent Panel for Pandemic Preparedness and Response.…”
Section: The Path(s) Forwardmentioning
confidence: 99%
“…The urgency to develop a COVID-19 vaccine led to unprecedented schedules that curtailed the standard vaccine development timeline [98]. The rapid development of COVID-19 vaccines has surpassed several unique challenges (safety, efficacy, dose regimen, stability, and storage characteristics) and began at the time of isolation and identification of the SARS-CoV-2 viral genetic sequence [99]. Furthermore, challenges such as national lockdowns and physical distancing directly increased the concerns over the safety of the vaccines.…”
Section: Vaccines and Dmmentioning
confidence: 99%
“…In phase III clinical trials, several vaccines worldwide have demonstrated efficacy of higher than 95% in prevention of COVID-19 infection. To date, at least ten vaccines have been authorized for public use (full or emergency) and as of 21 May 2021, over 700 million doses (counted as a single dose, and may not equal the total number of people vaccinated) have been administered worldwide (Table 3) The WHO has recommended that people with comorbidities that have been identified as being at an increased risk of severe COVID-19, including obesity, cardiovascular disease, respiratory disease, and DM, receive COVID-19 vaccines [99]. However, researchers have pointed out an important caveat of elevated levels of blood glucose for diabetic individuals post-vaccine administration due to higher energy consumption in response to immune functions [102].…”
Section: Vaccines and Dmmentioning
confidence: 99%
“…Besides regulatory authorizations or approvals of COVID-19 vaccines, antivirals, and neutralizing antibodies in various countries, there remains a global need to develop additional safe, effective, easy-to-produce, and inexpensive treatments to prevent or reduce the risk of acquiring severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection ( 21 , 22 ). This need is of heightened importance for health care and other at-risk service workers in regions where new variants of SARS-CoV-2 may increase contagiousness or evade immunity produced by vaccines or previous infection ( 23 , 24 ) or where COVID-19 vaccination is unavailable.…”
Section: Diagnosis and Treatment Of Viral Infectionsmentioning
confidence: 99%